Evaluation of antiproliferative activity of chalcone and dihydrochalcone extract from artocarpus lowii leaves on breast cancer cell lines - Mahmud, Norliana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Artocarpus species are rich in phenolic compounds including flavonoids, stilbenoids, arylbenzofurons and Jacalin which support their pharmacological properties as a medicinal sources. Previous pharmacological studies of the natural products from Artocarpus sp have established their mode of action in treatment of various diseases and other health benefits. Therefore, in this study two flavonoid compounds from Artocarpus lowii, 2,4-dihydroxy-4- methoxy-3prenyldihydrochalcone ( dihydrochalcone) and 2,4-dihydroxy-3,4-(2,2- dimethylchromene)chalcones (chalcone) were tested for antiproliferative activity on human adenocarcinoma breast cancer cell lines, MCF-7 and MDA-MB-23 I. The findings showed that both of the compounds, dihydrochalcone and chalcone had IC50 lower than 20 ~g/mL which were of good cancer therapeutic value on the above mention cancer cell lines. However, dihydrochalcone had the best IC50 value which was 1.023 ~g/mL on MCF-7 cell line. This compound also inhibits the growth of normal cell line, L929 but at higher IC50 value which is 1.659 ~g/mL. Mode of cell death caused by the compound was further tested by using Hoechst 33258 staining for apoptosis . The apoptotic features were seen in the treated cancer cells. Flow cytometry analysis also had been done as complement to Hoechst staining which revealed a small number of apoptotic cells. It is concluded that dihydrochalcone compound from A.lowii exert anticancer effect on MCF-7 breast cancer cell line through apoptosis. The results inspire future advanced studies in order to produce an anticancer drug from this plant.